2007
DOI: 10.1002/qua.21483
|View full text |Cite
|
Sign up to set email alerts
|

Periodic models in quantum chemical simulations of F centers in crystalline metal oxides

Abstract: ABSTRACT:We present a survey of recent first principles simulations of the neutral oxygen vacancies (F centers) existing as native or radiation-induced point defects in various crystalline metal oxides in different forms (bulk, bare substrate surface, and on the interface with metal adsorbates). We mainly consider periodic models in calculations of point defects using the metal oxide supercell or cyclic clusters. We compare different formalisms of first principles calculations, mostly the Density Functional Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 205 publications
(458 reference statements)
3
42
1
Order By: Relevance
“…Upon formation of the oxygen vacancy, the DOS exhibits a state in the gap as corresponds to an F-center, located above the valence band by 2.57 eV (PBE) , 3.06 eV (B3LYP). This is in good agreement with experimental and comparable theoretical results [88,89,87].…”
Section: Mgo (Ir2)supporting
confidence: 92%
See 2 more Smart Citations
“…Upon formation of the oxygen vacancy, the DOS exhibits a state in the gap as corresponds to an F-center, located above the valence band by 2.57 eV (PBE) , 3.06 eV (B3LYP). This is in good agreement with experimental and comparable theoretical results [88,89,87].…”
Section: Mgo (Ir2)supporting
confidence: 92%
“…The Mg 2+ and O 2-ions are octahedral and the bonding is highly ionic. The measured band gap in magnesium oxide is 7.8 eV [87]. Our PBE value of 4.77 eV, although underestimates the experimental one as expected from DFT-GGA, clearly reproduces the energetic gap of an insulating system.…”
Section: Mgo (Ir2)supporting
confidence: 58%
See 1 more Smart Citation
“…The structural and electronic properties of oxygen vacancy in both the bulk and on the surface of STO were illustrated detailedly in Ref. [45]. Meanwhile, the structure of Au 0 O is also energetically favorable, which may be attributed to the highest electron affinity of Au atoms and electron transfer from electron-rich oxygen vacancy sites into Au atoms [46].…”
Section: Defective Sto(0 0 1) Surfacementioning
confidence: 98%
“…59), 60) In MgO crystals, it has been demonstrated that there exist two principal oxygen vacancies, namely, the F + (an oxygen vacancy occupied by one electron) and F (an oxygen vacancy occupied by two electrons) color centers, which are oxygen vacancies with one and two electrons, respectively. Both the F + and F color centers absorb essentially the same energy of ³5 eV (³250 nm) but show different photoluminescence (PL) bands peaked at ³400 and ³500 nm, respectively.…”
Section: Magnesia (Mgo)mentioning
confidence: 99%